2009
DOI: 10.1021/ja9033473
|View full text |Cite
|
Sign up to set email alerts
|

Direct Interaction between Amphotericin B and Ergosterol in Lipid Bilayers As Revealed by 2H NMR Spectroscopy

Abstract: Although amphotericin B (AmB) is thought to exert its antifungal activity by forming transmembrane ion-permeable self-assemblies together with ergosterol, no previous study has directly proven AmB-ergosterol interaction. To establish the interaction, we measured (2)H NMR using deuterium-labeled sterols and AmB. The (2)H NMR spectra of deuterated ergosterol in palmitoyloleoylphosphatidylcholine (POPC) bilayers showed that fast axial diffusion of erogosterol was almost completely inhibited by the coexistence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
89
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(95 citation statements)
references
References 45 publications
5
89
0
Order By: Relevance
“…17 Multicomponent systems are also important, probing the role of functional groups in aggregation [18][19][20] and drug delivery. [21][22][23][24] A number of physical techniques can provide information on aggregation processes such as optical absorption, 3 x-ray scattering 3,13,25,26 and nuclear magnetic resonance (NMR) spectroscopy. 10,12,[26][27][28] In general, absorption and scattering based experiments provide information on the bulk properties of a sample, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…17 Multicomponent systems are also important, probing the role of functional groups in aggregation [18][19][20] and drug delivery. [21][22][23][24] A number of physical techniques can provide information on aggregation processes such as optical absorption, 3 x-ray scattering 3,13,25,26 and nuclear magnetic resonance (NMR) spectroscopy. 10,12,[26][27][28] In general, absorption and scattering based experiments provide information on the bulk properties of a sample, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…At this stage, cells satisfy their sterol requirements through dietary supplementation of cholesterol via lipoproteins in full-growth medium (FGM) present in the blood meal ( 10,11 ). Consequently, the existence of a sterol uptake process which permits the formation of BSF membranes containing exclusively cholesterol could provide resistance to a range of antifungal drugs, e.g., amphotericin B, that function typically in membranes formed by ergosterol ( 14,15 ). However, all the genes for ergosterol biosynthesis have been found recently to be expressed in BSF ( 16,17 ) and inhibitors of the post-squalene portion of ergosterol biosynthesis can inhibit growth of BSFs ( 4,(18)(19)(20); therefore, the ability for BSFs to grow as an ergosteroldepleted protozoan with dietary cholesterol as an ergosterol surrogate remains enigmatic.…”
mentioning
confidence: 99%
“…For example, many computational (11-13, 29, 36, 37) and spectroscopic (9,10,15,34,39,40) studies have been reported, but the membrane-localized, dynamic, and multimolecular nature of this small-molecule-based channel assemblage challenges the current limitations of these techniques. In addition, many studies have been performed with AmB derivatives having covalent modifications of the C41 carboxylic acid and/ or C(3′) amine (14,19,(31)(32)(33)(34)(35)(44)(45)(46).…”
mentioning
confidence: 99%
“…It is challenging, however, to perform this same experiment in a yeast cell membrane to determine if this type of direct binding interaction is functionally relevant in vivo. More recently, solid-state NMR studies employing deuterated derivatives of AmB and cholesterol (39, 40) suggested little or no binding between these two molecules because their mobilities were dissimilar (40). Analogous experiments with AmB and ergosterol were interpreted as being alternatively consistent with similar mobilities and thus supportive of a direct binding interaction between these two molecules (40).…”
mentioning
confidence: 99%
See 1 more Smart Citation